A positive electrode material of a lithium ion battery, a preparation method and application thereof
Patent Information
- Application Number
- CN202310206757.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-28
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-02-28
AI Technical Summary
Existing lithium-ion battery cathode materials suffer from low energy density, insufficient rate performance, and inadequate cycle performance. In particular, hollow structure materials have low particle strength, which affects the cycle performance and safety of lithium-ion batteries.
By controlling the internal porosity and surface roughness of the cathode material, the internal porosity of the secondary particles is 1%≤P≤15%, and the surface roughness is 10nm≤Z≤1μm. The lithium-ion transport path is optimized, and the cathode material is prepared by controlling the sintering process, resulting in a material with excellent energy density, rate performance, and safety performance.
It improves the energy density, rate performance, and cycle performance of lithium-ion batteries, while enhancing safety performance, avoiding breakage and gas generation of the positive electrode during the rolling process, providing a buffer space during the lithium insertion/extraction process, and improving battery stability.
Smart Images

Figure CN116031393B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a positive electrode material for lithium-ion batteries, its preparation method, and its application. Background Technology
[0002] With the development of society and technology, humanity's over-reliance on and consumption of fossil fuels has led to the global energy crisis. Therefore, countries around the world are searching for renewable and clean new energy sources, such as solar, wind, geothermal, tidal, and bioenergy. However, these new energy sources have drawbacks, including low energy density, intermittency and randomness, and require robust energy storage systems.
[0003] Lithium-ion batteries possess advantages such as high energy density, high operating voltage, low self-discharge rate, and long lifespan, making them a recognized environmentally friendly and efficient energy storage system. A lithium-ion battery mainly consists of a positive electrode, a negative electrode, a separator, and an electrolyte. Discharging and charging of lithium-ion batteries primarily rely on the movement of lithium ions between the positive and negative electrodes.
[0004] As an important component of the positive electrode, the positive electrode material provides lithium ions that move back and forth between the positive and negative electrodes during the charging and discharging process of lithium-ion batteries. Therefore, the properties of the positive electrode material are crucial to the performance of lithium-ion batteries.
[0005] Currently, most commercially available lithium nickel cobalt manganese oxide cathode materials are solid structures. This results in insufficient contact between the cathode material and the electrolyte, leading to a long lithium-ion transport path and insufficient high-rate charge / discharge performance and power performance. While hollow cathode materials have a large specific surface area, increasing the contact area between the cathode material and the electrolyte to some extent improves the rate and power performance of lithium-ions, they have lower compaction density and energy density. Furthermore, the particle strength of hollow materials is relatively low, making them prone to breakage during cathode sheet rolling, which affects the cycle performance of lithium-ion batteries. Summary of the Invention
[0006] To address the aforementioned technical problems, this invention provides a positive electrode material for lithium-ion batteries. By controlling the internal porosity and surface roughness of the positive electrode material, the lithium-ion batteries prepared from this positive electrode material possess excellent energy density, rate performance, cycle performance, and safety performance.
[0007] The present invention also provides a method for preparing a positive electrode material for a lithium-ion battery. The positive electrode material prepared by this method is applied to a lithium-ion battery, which has excellent energy density, rate performance, cycle performance and safety performance.
[0008] The present invention also provides a positive electrode sheet and a lithium-ion battery including the positive electrode sheet. The positive electrode sheet includes the above-mentioned positive electrode material. Therefore, the lithium-ion battery assembled from the positive electrode sheet has excellent energy density, rate performance and cycle performance.
[0009] In a first aspect, the present invention provides a positive electrode material for a lithium-ion battery, wherein the positive electrode material is a secondary particle, the internal porosity P of the secondary particle is 1% ≤ P ≤ 15%, and the surface roughness Z is 10 nm ≤ Z ≤ 1 μm.
[0010] In some embodiments, the internal porosity P of the secondary particles is 2% ≤ P ≤ 11%, preferably 5% ≤ P ≤ 10%.
[0011] In some embodiments, the surface roughness Z of the secondary particles is 10nm≤Z≤500nm, preferably 100nm≤Z≤500nm.
[0012] In some embodiments, the pore size D of the internal pores of the secondary particles is D≤2μm, preferably D≤500nm; and / or
[0013] The uniformity A of the internal pores of the secondary particles is 0.7≤A≤1.3, preferably 0.8≤A≤1.2.
[0014] In some embodiments, the secondary particles have a BET specific surface area of 0.2–1.0 m². 2 / g; and / or
[0015] The median particle size Dv50 of the cathode material is 8.5 μm ≤ Dv50 ≤ 11.5 μm.
[0016] In some embodiments, the cathode material includes a core material, the core material comprising Li a Ni b Co c M 1-b-c O2, a is 0.8–1.2, b is 0.5–0.92, c is 0–0.5, and M is selected from at least one of Mn, Al, and V.
[0017] In some implementations, a is 0.95-1.05; and / or
[0018] b is 0.6-0.92; and / or
[0019] c is 0-0.3.
[0020] In a second aspect, the present invention provides a method for preparing the positive electrode material of the lithium-ion battery provided in the first aspect, the preparation method comprising the following steps:
[0021] 1) A precipitant and a complexing agent are introduced into a metal salt solution to make the concentration of the complexing agent in the system 1-6 g / L, and a co-precipitation reaction is carried out under the condition of pH 10-13. After aging, the precursor of the cathode material is obtained.
[0022] 2) The precursor is mixed with a lithium source and subjected to a first sintering to obtain a first sintering product; the first sintering is divided into a first stage sintering and a second stage sintering, the first stage sintering temperature is 300-600℃ and the holding time is 1-15h, the second stage sintering temperature is 650-900℃ and the holding time is 3-20h.
[0023] 3) The first sintering product is subjected to a second sintering to obtain the cathode material.
[0024] In some implementations, in step 1), the pH of the system is 11-12.5; and / or
[0025] The concentration of the complexing agent in the system is 3-5 g / L.
[0026] In some implementations, in step 2), the first sintering temperature is 350–550°C, and the holding time is 1–10 h, preferably 4–9 h; the second sintering temperature is 650–900°C, and the holding time is 8–17 h.
[0027] In some embodiments, in step 1), the complexing agent is ammonia water, the concentration of the ammonia water is 1 to 15 mol / L, and the flow rate of the ammonia water is 10 to 500 L / h.
[0028] In step 1), the concentration of the precipitant is 1 to 10 mol / L, and the flow rate is 10 to 500 L / h.
[0029] In some embodiments, in step 1), the coprecipitation reaction is carried out under stirring at a rate of 200–500 r / min; and / or
[0030] In step 1), the temperature of the coprecipitation reaction is 45–70°C, and the time is 20–100 hours.
[0031] In some embodiments, in step 1), the precipitant is selected from sodium hydroxide, sodium carbonate, ammonium carbonate, and ammonium oxalate.
[0032] In some embodiments, in step 1), the salt solution contains a nickel source, a cobalt source, and an M source, and the total concentration of nickel, cobalt, and M metal ions is 0.5–3 mol / L.
[0033] In some embodiments, in step 1), the nickel source is selected from nickel sulfate, nickel nitrate, and nickel chloride, or combinations thereof; and / or
[0034] In step 1), the cobalt source is selected from cobalt sulfate, cobalt nitrate, and cobalt chloride, or a combination thereof; and / or
[0035] In step 1), the source M is selected from manganese sulfate, manganese nitrate, manganese chloride, aluminum sulfate, aluminum nitrate, aluminum chloride, vanadium sulfate, vanadium nitrate, and vanadium chloride, or a combination thereof.
[0036] In some implementations, in step 3), the first sintering product is first mixed with the material of the coating layer, and then a second sintering is performed.
[0037] Thirdly, the present invention provides a positive electrode sheet, the positive electrode sheet comprising the positive electrode material provided in the first aspect or the positive electrode material prepared by the preparation method provided in the second aspect.
[0038] Fourthly, the present invention provides a lithium-ion battery, the lithium-ion battery comprising the positive electrode provided in the third aspect.
[0039] The implementation of this invention has at least the following beneficial effects:
[0040] The positive electrode material for lithium-ion batteries provided by this invention, by controlling the internal porosity P of the secondary particles to be 1% ≤ P ≤ 15% and the surface roughness Z to be 10 nm ≤ Z ≤ 1 μm, not only ensures sufficient contact between the positive electrode material and the electrolyte, resulting in a shorter lithium-ion transport path, but also minimizes the contact area between the positive electrode material and the electrolyte, reducing side reactions and gas generation. This improves the rate performance of the lithium-ion battery prepared from the positive electrode material, and also results in a higher compaction density of the prepared positive electrode sheet, leading to a higher energy density of the lithium-ion battery. Simultaneously, during rolling, the secondary particles are prevented from being crushed, thus avoiding increased gas generation in the positive electrode sheet, resulting in excellent cycle performance of the lithium-ion battery. Furthermore, the internal pores provide a buffer space for expansion / contraction during lithium insertion / extraction, preventing damage such as liquid swelling deformation of the positive electrode sheet, thereby improving the safety performance of the lithium-ion battery. Attached Figure Description
[0041] Figure 1 This is a cross-sectional SEM image of the ternary cathode material provided in Embodiment 1 of the present invention;
[0042] Figure 2 The porosity uniformity measurement profile and region division diagram provided by the present invention. Detailed Implementation
[0043] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions in the embodiments of this invention will be clearly and completely described below in conjunction with the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0044] The first aspect of the present invention provides a positive electrode material for a lithium-ion battery, wherein the positive electrode material is a secondary particle, the internal porosity P of the secondary particle is 1% ≤ P ≤ 15%, and the surface roughness Z is 10 nm ≤ Z ≤ 1 μm.
[0045] In this invention, the roughness of secondary particles is used to characterize the external pore distribution of the secondary particles. By controlling the internal porosity P of the secondary particles to be 1% ≤ P ≤ 15% and the surface roughness Z to be 10 nm ≤ Z ≤ 1 μm, not only is sufficient contact between the cathode material and the electrolyte achieved, resulting in a shorter lithium-ion transport path, but the contact area between the cathode material and the electrolyte is also reduced, thereby reducing side reactions and gas production. This improves the rate performance of the lithium-ion battery prepared from the cathode material. Furthermore, the prepared cathode sheet has a higher compaction density, resulting in a higher energy density for the lithium-ion battery. Simultaneously, during rolling, the secondary particles are prevented from being crushed, thus avoiding increased gas production in the cathode sheet and ensuring excellent cycle performance of the lithium-ion battery. Moreover, the internal pores provide a buffer space for expansion / contraction during lithium insertion / extraction, preventing damage such as liquid swelling deformation of the cathode sheet and improving the safety performance of the lithium-ion battery.
[0046] In this invention, the term "secondary particle" refers to a particle composed of aggregates of multiple primary particles. The secondary particles of this invention have a spherical or near-spherical shape, such as an ellipsoid.
[0047] In this invention, the term "internal pores" refers to pores in secondary particles that are not connected to the outside world, i.e., closed pores.
[0048] The term "internal porosity" in this invention refers to the percentage of the volume of internal pores in a secondary particle in the total volume of the secondary particle.
[0049] In this invention, the term "surface roughness" refers to the unevenness of a material surface, characterized by small spacing and minute peaks and valleys. The distance between adjacent peaks and valleys (wavelength) is very small, typically less than 1 μm. It falls under the category of microscopic geometric errors. The smaller the surface roughness of a material, the smoother the surface.
[0050] The cathode material of the lithium-ion battery provided by this invention can be a binary cathode material or a ternary cathode material.
[0051] In one embodiment, the internal porosity P of the secondary particles is 2% ≤ P ≤ 11%.
[0052] In one embodiment, the internal porosity P of the secondary particles is 5% ≤ P ≤ 10%.
[0053] By optimizing the internal porosity of the secondary particles, the cathode material and electrolyte are brought into full contact, optimizing the lithium-ion transport path. At the same time, the contact area between the cathode material and electrolyte is minimized, reducing side reactions and gas production, thus improving the rate performance of the lithium-ion battery. Furthermore, the compaction density is increased, thereby improving the energy density of the lithium-ion battery. The strength of the secondary particles is also improved, ensuring the cycle performance of the lithium-ion battery. In addition, a certain buffer space is provided for the expansion / contraction during charging / discharging, preventing damage such as liquid swelling deformation of the cathode sheet, thus improving the safety performance of the lithium-ion battery.
[0054] In one implementation, the surface roughness Z of the secondary particles is 10nm ≤ Z ≤ 500nm. By optimizing the surface roughness of the cathode material, the lithium-ion transport path is optimized, the contact area between the cathode material and the electrolyte is reduced, side reactions are reduced, gas production is decreased, and the rate performance, cycle performance, and safety performance of the battery are improved.
[0055] In one embodiment, the surface roughness Z of the positive electrode material is 100nm≤Z≤500nm.
[0056] In one embodiment, the internal porosity P of the secondary particles is 2% ≤ P ≤ 11%, and the surface roughness Z is 10nm ≤ Z ≤ 500nm.
[0057] In one implementation, the internal porosity P of the secondary particles is 5% ≤ P ≤ 10%, and the surface roughness Z is 100 nm ≤ Z ≤ 500 nm. The combination of internal porosity and surface roughness of the secondary particles not only ensures sufficient contact between the cathode material and the electrolyte, resulting in a shorter lithium-ion transport path, but also minimizes the contact area between the cathode material and the electrolyte, reducing side reactions and gas generation. This improves the rate performance of the lithium-ion battery prepared from the cathode material, and also results in a higher compaction density of the prepared cathode sheet, leading to a higher energy density of the lithium-ion battery. Simultaneously, during rolling, the secondary particles are prevented from being crushed, thus avoiding increased gas generation in the cathode sheet, resulting in excellent cycle performance of the lithium-ion battery. Furthermore, the internal pores provide a buffer space for expansion / contraction during lithium insertion / extraction, preventing damage such as liquid swelling deformation of the cathode sheet, thereby improving the safety performance of the lithium-ion battery.
[0058] In one implementation, the pore size D of the internal pores of the secondary particles is D≤2μm. By optimizing the pore size of the internal pores of the secondary particles, the integrity of the secondary particle structure during rolling is ensured, and the internal stress change of the positive electrode sheet during lithium-ion battery cycling can be reduced, thereby reducing the impact of material pulverization on the cycle performance and safety performance of the lithium-ion battery.
[0059] In one embodiment, the pore size D of the internal pores of the secondary particles is 10nm≤D≤500nm.
[0060] In one implementation, the uniformity A of the internal pores of the secondary particles is 0.7 ≤ A ≤ 1.3. The more uniform the distribution of the internal pores of the secondary particles, the more uniform the stress experienced by the prepared positive electrode during cycling, the better the stability, the more cycles can be performed, and correspondingly, the better the cycle performance of the lithium-ion battery.
[0061] In one embodiment, the uniformity A of the internal pores of the secondary particles is 0.8 ≤ A ≤ 1.2.
[0062] In one embodiment, the pore size D of the internal pores of the secondary particles is 1 nm ≤ D ≤ 2 μm, preferably 10 nm ≤ D ≤ 500 nm; and the uniformity A of the internal pores of the secondary particles is 0.7 ≤ A ≤ 1.3, preferably 0.8 ≤ A ≤ 1.2. The pore size distribution range of the internal pores of the secondary particles is relatively narrow, and the pore size is small. The higher the uniformity of the internal pores, the higher the stability of the cathode material. During lithium-ion battery cycling, the internal stress of the cathode sheet is small and uniform, resulting in better rate performance and cycle performance of the prepared lithium-ion battery, as well as higher compaction density and higher energy density.
[0063] In one embodiment, the BET specific surface area of the positive electrode material is 0.2–1.0 m². 2 / g. A BET specific surface area within this range indicates that the cathode material particles are of moderate size, balancing energy density and rate performance. It avoids the problems of excessively large BET specific surface areas and numerous small-to-medium particle sizes leading to low compaction density, severe gas generation, and low energy density, while also preventing excessively small BET specific surface areas and numerous large-to-medium particle sizes from causing reduced rate performance. Furthermore, the combination of BET specific surface area within this range with porosity and roughness can further effectively improve the cathode material's adsorption capacity for electrolyte, thereby improving the rate performance and cycle performance of lithium-ion batteries, and ultimately enhancing the electrical performance of lithium-ion batteries.
[0064] In this invention, the term "BET specific surface area" refers to the total area per unit mass of material.
[0065] In one implementation, the median particle size Dv50 of the cathode material is 8.5 μm ≤ Dv50 ≤ 11.5 μm. By optimizing the median particle size of the cathode material, the compaction density of the cathode material is increased, thereby improving the energy density of the lithium-ion battery. At the same time, the distance of the solid-phase diffusion path of lithium ions is optimized, further improving the rate performance of the lithium-ion battery.
[0066] In one embodiment, the particle size of the cathode material is Dv10 ≥ 4 μm, 8.5 μm ≤ Dv50 ≤ 11.5 μm, and Dv90 ≤ 22 μm. Particle sizes within different distribution ranges can further increase the compaction density of the cathode material, thereby improving the energy density of the lithium-ion battery and optimizing the distance of the solid-phase diffusion path of lithium ions, thus improving the rate performance of the lithium-ion battery.
[0067] In one embodiment, the tap density TD of the positive electrode material is TD≥2.2g / cm³. 3 The higher the tap density, the more cathode material per unit volume, and the higher the energy density.
[0068] In one embodiment, the tap density TD of the positive electrode material is 2.3 g / cm³. 3 ≤TD≤2.8g / cm 3 .
[0069] The term "tapered density" in this invention refers to the mass per unit volume of powder in a container after it has been tapped under specified conditions.
[0070] In one embodiment, the cathode material includes a core material, the core material being composed of Li. a Ni b Co c M 1-b-c O2, a is 0.8–1.2, b is 0.5–0.92, c is 0–0.5, and M is selected from Mn, Al, and V or combinations thereof. In this invention, the addition ratio of nickel increases the energy density of the lithium-ion battery; the addition ratio of cobalt stabilizes the layered structure of the cathode material, improves the cycle life and rate performance of the lithium-ion battery prepared from it, and reduces the impact on the specific capacity of the lithium-ion battery; the addition ratio of manganese, aluminum, and vanadium or combinations thereof not only improves the structural stability of the cathode material and the safety of the lithium-ion battery prepared from it, but also reduces the material cost of the lithium-ion battery, while reducing the impact on the specific capacity. Therefore, by selecting the composition ratio of lithium, nickel, cobalt, manganese, aluminum, and vanadium or combinations thereof in the core material of the cathode material, the energy density, cycle performance, rate performance, and safety performance of the lithium-ion battery prepared from the cathode material are all taken into account.
[0071] The cathode material of the lithium-ion battery of the present invention can be a binary cathode material or a ternary cathode material.
[0072] In one implementation, α is 0.95-1.05. Lithium in this range can improve the energy density of lithium-ion batteries made from cathode materials.
[0073] In one implementation, b is 0.6-0.92. Nickel within this range can improve the energy density of lithium-ion batteries made from cathode materials.
[0074] In one implementation, c is 0-0.3. This range of M can improve the safety of lithium-ion batteries made from cathode materials while reducing the production cost of lithium-ion batteries.
[0075] In one embodiment, the cathode material further includes a coating layer covering at least a portion of the surface of the core material; the coating element in the coating layer is selected from at least one of the elements B, Ge, Na, Al, Si, Zr, Co, Ti, Mg, W, Sn, Ce, Mn, Y, Hf, Cu, Fe, Ag, La, In, Sc, Rh, V, or Zn. The coating layer forms a uniform and dense protective layer on the surface of the cathode material, preventing direct contact between the electrolyte and the cathode material, effectively limiting the corrosive effect of the electrolyte on the cathode material, protecting the electrode material without affecting the lithium-ion insertion / extraction rate, suppressing the dissolution of transition metals and the occurrence of side reactions, improving the stability of the cathode material structure and the lithium-ion conductivity, thereby improving the cycle performance and rate performance of the lithium-ion battery.
[0076] In one embodiment, the core material further includes a dopant element selected from at least one of B, Zr, Co, W, Y, In, Sc, Rh, V, or Zn. Cation doping can reduce the mixing degree of cations within the cathode material and effectively suppress phase transitions in the crystal during charge and discharge, thus improving the stability of the cathode material and consequently enhancing the electrochemical performance of the lithium-ion battery, especially its rate performance and cycle performance.
[0077] As one implementation, the coating element in the coating layer is in the Li a Ni b Co c M 1-b-c The mass percentage of O2 is 100–10,000 ppm.
[0078] As one implementation, the doping element is in the Li a Ni b Co c M 1-b-c The mass percentage of O2 is 100–30,000 ppm.
[0079] In one embodiment, the positive electrode material contains ≤3000ppm Li₂CO₃, ≤5000ppm LiOH, and ≤5000ppm Free Li + Content ≤2000ppm. Controlling the content of these impurities in the cathode material is to minimize the impact of residual alkali on the surface of the cathode material on gas production in lithium-ion batteries. In particular, a higher carbonate content will react with trace amounts of HF in the electrolyte to produce carbon dioxide and will also cause other side reactions. In addition, a high residual alkali content will cause it to react with polyvinylidene fluoride (PVDF) during the slurry preparation process, causing the slurry to gel and become jelly-like, thus affecting the use of the cathode material.
[0080] A second aspect of the present invention provides a method for preparing the above-mentioned cathode material, the method comprising the following steps:
[0081] 1) A precipitant and a complexing agent are introduced into a metal salt solution to make the concentration of the complexing agent in the system 1-6 g / L, and a co-precipitation reaction is carried out under the condition of pH 10-13, followed by aging for 10-100 hours to obtain the precursor of the cathode material;
[0082] 2) The precursor is mixed with a lithium source and subjected to a first sintering to obtain a first sintering product; the first sintering is divided into a first stage sintering and a second stage sintering, the first stage sintering temperature is 300-600℃ and the holding time is 1-15h, the second stage sintering temperature is 650-900℃ and the holding time is 3-20h.
[0083] 3) The first sintering product is subjected to a second sintering to obtain the cathode material.
[0084] In this invention, the second-stage sintering has a significant impact on the surface roughness of the crystal. Higher second-stage sintering temperatures result in faster crystal growth, leading to greater surface roughness and a coarser surface; conversely, lower second-stage sintering temperatures result in slower crystal growth, smaller crystals, and a smoother surface. Therefore, a second-stage sintering temperature of 650–900℃ and a holding time of 3–20 hours are selected. Specifically, if the temperature is below 650℃, secondary particles cannot be obtained; if the temperature is above 900℃, single-crystal particles are obtained.
[0085] The present invention provides a method for preparing a positive electrode material for lithium-ion batteries. By controlling the pH of the co-precipitation reaction system to 10-13 and the concentration of the complexing agent in the system to 1-6 g / L, the growth rate of grains during the co-precipitation reaction is controlled, resulting in a positive electrode material with an internal porosity P of 1% ≤ P ≤ 15%. Furthermore, the pH of the system and the concentration of the complexing agent are also related to the sphericity of the secondary particles. The sphericity of the secondary particles is related to their surface roughness. Therefore, a pH of 10-13 and a complexing agent concentration of 1-6 g / L are also beneficial for controlling the surface roughness of the secondary particles. Specifically, if the pH value is below 10, the precipitation reaction cannot be completed, and secondary particles cannot be obtained. If the pH value is above 13, the reaction rate is faster, the porosity increases, resulting in poor stability of the secondary particles, more internal pores, and poor gas production. If the ammonia value is greater than 6 g / L, the reaction rate is slower, crystal growth is slower, resulting in denser internal growth of secondary particles, lower porosity, and fewer ion conduction pathways, thus leading to poor rate performance of the battery. If the ammonia value is less than 1 g / L, co-precipitation is faster, resulting in looser crystal growth of secondary particles, higher internal porosity, and greater roughness, thus leading to poor cycle performance and poor gas production of the battery.
[0086] Furthermore, the surface roughness of the secondary particles is further adjusted through aging, and then the surface roughness of the secondary particles is further finely adjusted by controlling the temperature of the second stage sintering in the first sintering to be 650-900℃ and the holding time to be 3-20h. This makes the surface roughness Z of the cathode material approximately 10nm≤Z≤1μm, thereby enabling the cathode material to have excellent energy density, rate performance, cycle performance and safety performance.
[0087] The method for preparing the cathode material of lithium-ion batteries provided by this invention can prepare binary cathode materials or ternary cathode materials.
[0088] In one implementation, in step 2), the sintering temperature of the first stage is 300-600°C, and the holding time is 1-15 hours.
[0089] In one implementation, in step 2), the sintering temperature of the first stage is 350–550°C, and the holding time is 3–12 h.
[0090] In one implementation, in step 2), the temperature of the second sintering is 300-800°C, and the holding time is 1-15 hours.
[0091] In one embodiment, in step 1), the pH of the system is 11-12.5, and / or the concentration of the complexing agent in the system is 3-5 g / L. By optimizing the pH of the system and the concentration of the complexing agent in the system, the internal porosity of the secondary particles is made to be 2% ≤ P ≤ 11%, and further to 5% ≤ P ≤ 10%.
[0092] In one implementation, in step 2), the second sintering temperature is 700–780°C, and the holding time is 8–17 h. By optimizing the temperature and holding time of the second sintering in the first sintering, the roughness Z of the cathode material is controlled to be 10 nm ≤ Z ≤ 500 nm, and further to 100 nm ≤ Z ≤ 500 nm.
[0093] In one embodiment, the complexing agent is ammonia water, the concentration of which is 1–15 mol / L, and the flow rate of which is 10–500 L / h. By controlling the concentration and flow rate of the complexing agent, the concentration of the complexing agent in the reaction system is controlled, ensuring that the porosity P of the secondary particles is 1% ≤ P ≤ 15%, and that the pore size D of the internal pores of the secondary particles is D ≤ 2 μm, and further, D ≤ 500 nm.
[0094] In one embodiment, the concentration of the precipitant is 1–10 mol / L, and the flow rate of the precipitant is 10–500 L / h. By controlling the concentration and flow rate of the precipitant, not only can the pH of the system be precisely controlled, so that the porosity P of the secondary particles is 1% ≤ P ≤ 15%, but also the uniformity A of the internal pores of the secondary particles is 0.7 ≤ A ≤ 1.3.
[0095] In one embodiment, in step 1), the coprecipitation reaction is carried out under stirring conditions, and the stirring rate is 200–500 r / min. By controlling the pH of the system and the stirring rate, the uniformity A of the internal pores of the secondary particles is optimized to be 0.8 ≤ A ≤ 1.2.
[0096] In one embodiment, in step 1), the coprecipitation reaction is carried out under stirring conditions at a stirring rate of 200–500 r / min, and in step 1), the temperature of the coprecipitation reaction is 45–70 °C, and the time is 20–100 hours. By controlling the stirring rate, temperature, and time of the coprecipitation reaction, the median particle size Dv50 of the secondary particles is optimized to be 8.5 μm ≤ Dv50 ≤ 11.5 μm.
[0097] In one implementation method, after the coprecipitation reaction in step 1), the particles are aged for 10 to 100 hours. After 10 to 100 hours of aging, the sphericity of the secondary particles is significantly improved, thereby significantly reducing the surface roughness of the secondary particles.
[0098] In one embodiment, in step 1), the complexing agent is selected from ammonia, ammonia water, oxalic acid, ammonium sulfate, ammonium chloride, glycine, triethanolamine, polyacrylic acid, aminotrimethylmycin, sodium pyrophosphate, tartaric acid, ethylenediamine citrate, diethylenetriaminepentamethylmycinate, EDTA, aminotrimethylmycin, citric acid, ammonium citrate, and sodium citrate; and / or
[0099] In step 1), the precipitant is selected from sodium hydroxide, sodium carbonate, ammonium carbonate and ammonium oxalate.
[0100] In one embodiment, the salt solution contains a nickel source, a cobalt source, and an M source, with a total metal ion concentration of 0.5–3 mol / L for nickel, cobalt, and M. The method of this invention prepares a ternary cathode material.
[0101] In one embodiment, in step 1), the nickel source is selected from nickel sulfate, nickel nitrate, and nickel chloride, or a combination thereof; and / or
[0102] In step 1), the cobalt source is selected from cobalt sulfate, cobalt nitrate, and cobalt chloride, or a combination thereof; and / or
[0103] In step 1), the source M is selected from manganese sulfate, manganese nitrate, manganese chloride, aluminum sulfate, aluminum nitrate, aluminum chloride, vanadium sulfate, vanadium nitrate, and vanadium chloride, or a combination thereof.
[0104] In one embodiment, in step 3), the first sintering product is first mixed with the coating material, and then a second sintering is performed. This invention does not specifically limit the mixing method between the first sintering product and the coating material. Commonly used mixing methods in the art can be used; for example, a high-speed mixer can be used to mix the first sintering product and the coating material for a stirring time of 10–150 min, or more specifically, 20–50 min.
[0105] In one embodiment, the particle size of the coating material is 0.01–100 μm. Within this particle size range, the coating material has almost no impact on the surface roughness of the cathode material.
[0106] In one embodiment, the material of the coating layer is selected from at least one of oxides, phosphates or sulfates of the elements B, Ge, Na, Al, Si, Zr, Co, Ti, Mg, W, Sn, Ce, Mn, Y, Hf, Cu, Fe, Ag, La, In, Sc, Rh, V or Zn.
[0107] In one implementation, in step 2), the precursor is mixed with the dopant and lithium source, and then subjected to a first sintering. This invention does not specifically limit the mixing method of the precursor with the dopant and lithium source; any commonly used mixing method in the art can be used.
[0108] In one embodiment, the dopant is selected from at least one of oxides, fluorides, sulfides, phosphates, or sulfates of B, Zr, Co, W, Y, In, Sc, Rh, V, or Zn.
[0109] The present invention does not limit the sintering atmosphere; for example, the oxygen concentration can be maintained at more than 90% during the sintering process.
[0110] A third aspect of the present invention provides a positive electrode sheet, the positive electrode sheet comprising the positive electrode material provided in the first aspect or the positive electrode material prepared by the preparation method provided in the second aspect.
[0111] A fourth aspect of the present invention provides a lithium-ion battery, the lithium-ion battery comprising the positive electrode provided in the third aspect.
[0112] The lithium-ion battery assembled with the cathode material provided by this invention has a capacity retention rate of ≥90% after 300 1C charge-discharge cycles at 45°C.
[0113] In this invention, the internal porosity P, pore size D, uniformity A, surface roughness Z, and particle size of the positive electrode material of the lithium-ion battery are determined by the following method:
[0114] (1) The internal porosity P is calculated as follows: the size of the unit cell of the secondary particles is calculated by XRD, and the theoretical density ρ of the material is calculated by the mass of the atoms. 理 True density is measured using a true density meter. Helium gas is used to fill the surface of the material, but does not penetrate the internal pores. The density calculated by measuring the volume and mass of the cathode material is the true density, denoted as ρ. 真 , (ρ 理 -ρ 真 ) / ρ 理 Let be the internal porosity. Statistically analyze the cell dimensions of at least five secondary particles and calculate the average cell size.
[0115] (2) Calculation method of internal pore diameter D: The secondary particles of the positive electrode material are cut open using an argon ion polishing cutter (CP), and the pore size in at least 10 secondary particles is measured using SEM. The average value is calculated.
[0116] (3) Calculation method for the uniformity A of internal pores: The secondary particles are cut open using an argon ion polishing cutter (CP), and the cross-section is approximately circular, called the cross-sectional circle. Using Metis software, such as... Figure 2As shown, concentric circles are drawn with the center of the cross-sectional circle as the center, and the diameter of the concentric circles is the radius of the cross-sectional circle. Using Metis software, pores within the concentric circles are identified, and the area S1 of these pores is calculated. Similarly, pores at the annulus between the cross-sectional circle and the concentric circles are identified, and the area S2 of these pores is calculated. Since the area of the concentric circles is 1 / 3 of the area of the annulus, the uniformity of the internal pores is A = 3S1 / S2.
[0117] (4) The surface roughness of secondary particles is measured using a surface roughness meter.
[0118] (5) The BET specific surface area was measured by the BET specific surface area test method.
[0119] (6) The particle size was measured using a Malvern laser particle size analyzer.
[0120] (7) The tapped density was measured using a tapped density meter.
[0121] (8) Li₂CO₃, LiOH, and Free Li in the cathode material + Content measurement method: acid-base titration.
[0122] The cathode material and lithium-ion battery of the present invention will be described in detail below through specific embodiments.
[0123] Example 1
[0124] This embodiment provides a method for preparing a ternary cathode material. The preparation method includes the following steps:
[0125] In this embodiment, the nickel source is nickel sulfate, the M source is manganese sulfate, the cobalt source is cobalt sulfate, the complexing agent is 5 mol / L ammonia water, the precipitant is 2 mol / L sodium hydroxide, the lithium source is lithium hydroxide, the dopants are zirconium dioxide and cerium dioxide, and the coating material is aluminum oxide and boron oxide.
[0126] 1) Nickel source, cobalt source, M source, and water were mixed to obtain a salt solution with a total metal content of 2 mol / L, wherein nickel, cobalt, and manganese were mixed in a molar ratio of 0.92:0.07:0.01. The salt solution was placed in a reactor, and a precipitant and complexing agent were added to the salt solution to carry out a co-precipitation reaction. The concentration of ammonia water was 5 mol / L, the flow rate of ammonia water was 50 L / h, and the ammonia value in the system was controlled at 4.8 g / L. The pH value of the system was adjusted using sodium hydroxide solution with a concentration of 2 mol / L and a flow rate of 80 L / h to adjust the pH value to 12.1. During precipitation, uniform stirring was used to ensure uniform growth of material particles. The stirring speed was 300 r / min, and the water temperature was controlled at 55℃. After reacting for 36 h, the mixture was aged for 45 h to obtain the precursor Ni. 0.92 Co0.07 Mn 0.01 (OH)2.
[0127] 2) Mix the precursor and lithium source at a molar ratio of 1:1.06, then add 1200ppm ZrO2 and 800ppm CeO2 and mix evenly to obtain a mixture.
[0128] 3) Pass the mixture through a 200-400 mesh sieve, and then load the mixture into a sagger. Process it using the following sintering process: I. Sintering is divided into two stages, during which the oxygen concentration needs to be maintained above 90%. In the first sintering stage, the sintering temperature is 540℃, and the holding time is 8 hours. The second sintering temperature is 720℃, and the holding time is 15 hours, yielding the first sintered product.
[0129] 4) After crushing the first sintering product, mix it with water at a ratio of 1:1 and wash it for 3 minutes. The stirring speed is 600 r / min. After washing, filter the product by suction filtration to obtain a filter cake. Dry the filter cake at a certain temperature of 160℃.
[0130] 5) After drying, the first sintering product is crushed and sieved, and then mixed with the coating material. The specific addition ratio is 2100ppm Al2O3 and 2800ppm B2O3. The mixture is mixed in a high-speed mixer for 15 minutes.
[0131] 6) The mixture obtained in step 5) is placed into a sagger and subjected to a second sintering. The second sintering temperature is 345℃, and the holding time is 10 hours. It is then cooled to room temperature in the furnace, and finally cooled to room temperature again to obtain the ternary cathode material. A cross-sectional view of the secondary particles of this ternary cathode material is shown below. Figure 1 As shown.
[0132] Example 2
[0133] The preparation process of Example 2 is basically the same as that of Example 1, except that in step 1), the ammonia value in the system is controlled at 4.1 g / L and the pH value of the system is 12, while other conditions remain unchanged.
[0134] Example 3
[0135] The preparation process of Example 3 is basically the same as that of Example 1, except that in step 1), the ammonia value in the system is controlled at 3.2 g / L and the pH value of the system is 12.2, while other conditions remain unchanged.
[0136] Example 4
[0137] The preparation process of Example 4 is basically the same as that of Example 1, except that in step 1), the ammonia value in the system is controlled at 2 g / L and the pH value of the system is 12, while other conditions remain unchanged.
[0138] Example 5
[0139] The preparation process of Example 5 is basically the same as that of Example 1, except that the ammonia value in the system is 1 g / L and the pH value of the system is 11.9 in step 1), while other conditions remain unchanged.
[0140] Example 6
[0141] The preparation process of Example 6 is basically the same as that of Example 1, except that the flow rate of ammonia water in step 1) is 300 L / h and the ammonia value in the system is controlled at 3.2 g / L, while other conditions remain unchanged.
[0142] Example 7
[0143] The preparation process of Example 7 is basically the same as that of Example 1, except that in step 1), the ammonia value in the system is controlled at 3.2 g / L and the flow rate of the precipitant is 280 L / h, while other conditions remain unchanged.
[0144] Example 8
[0145] This embodiment provides a method for preparing a ternary cathode material. The preparation method includes the following steps:
[0146] In this embodiment, the nickel source is nickel sulfate, the M source is manganese sulfate, the cobalt source is cobalt sulfate, the complexing agent is 4 mol / L ammonia water, the precipitant is 3 mol / L sodium hydroxide, the lithium source is lithium hydroxide, the dopants are strontium oxide and zirconium dioxide, and the coating layer material is zirconium dioxide and boron trioxide.
[0147] 1) Nickel source, cobalt source, M source, and water were mixed to obtain a salt solution with a total metal content of 2 mol / L, wherein nickel, cobalt, and manganese were mixed in a molar ratio of 0.9:0.05:0.05. The salt solution was placed in a reactor, and a precipitant and complexing agent were added to it for co-precipitation. The concentration of ammonia water was 4 mol / L, the flow rate of ammonia water was 45 L / h, and the ammonia value in the system was controlled at 5.6 g / L. The pH value was adjusted using a sodium hydroxide solution as a precipitant, with a concentration of 3 mol / L and a flow rate of 78 L / h. The pH value was controlled within the range of 11.5. Uniform stirring was used during precipitation to ensure uniform particle growth. The stirring speed was 300 r / min, and the water temperature was controlled at 55℃. After reacting for 36 h, the mixture was aged for 45 h to obtain the precursor Ni. 0.9 Co 0.05 Mn 0.05 (OH)2.
[0148] 2) Mix the precursor and lithium source at a molar ratio of 1:1.06, then add 1000ppm SrO and 500ppm ZrO2 and mix evenly to obtain a mixture.
[0149] 3) Pass the mixture through a 200-400 mesh sieve, and then load the mixture into a sagger. Process it using the following sintering process: I. Sintering is divided into two stages, during which the oxygen concentration needs to be maintained above 90%. In the first sintering stage, the sintering temperature is 540℃, and the holding time is 8 hours. The second sintering temperature is 758℃, and the holding time is 15 hours, yielding the first sintered product.
[0150] 4) After crushing the first sintering product, mix it with water at a ratio of 1:1 and wash it for 3 minutes. The stirring speed is 600 r / min. After washing, filter the product by suction filtration to obtain a filter cake. Dry the filter cake at a certain temperature of 160℃.
[0151] 5) After drying, the first sintering product is crushed and sieved, and then mixed with the coating material. The specific addition ratio is 3000ppm B2O3 and 3500ppm ZrO2. The mixture is mixed in a high-speed mixer for 15 minutes.
[0152] 6) The mixture obtained in step 5) is placed into a sagger and subjected to a second sintering. The temperature of the second sintering is 345℃, the holding time is 10 hours, and then the mixture is cooled to room temperature with the furnace. Finally, the mixture is cooled to room temperature with the furnace to obtain the ternary cathode material.
[0153] Example 9
[0154] The preparation process of Example 9 is basically the same as that of Example 8, except that in step 1), the ammonia value in the system is controlled at 4.3 g / L and the pH value of the system is adjusted to 11.6, while other conditions remain unchanged.
[0155] Example 10
[0156] The preparation process of Example 10 is basically the same as that of Example 8, except that in step 1), the ammonia value in the system is controlled to be 2.3 g / L and the pH value of the system is adjusted to 11.6, while other conditions remain unchanged.
[0157] Example 11
[0158] The preparation process of Example 11 is basically the same as that of Example 8, except that in step 1), the ammonia value in the system is controlled to be 1.4 g / L and the pH value of the system is adjusted to 11.4, while other conditions remain unchanged.
[0159] Example 12
[0160] The preparation process of Example 12 is basically the same as that of Example 8, except that the concentration of ammonia water in step 1) is 0.5 mol / L, the ammonia value in the system is controlled at 4.3 g / L, the pH value of the system is adjusted to 12.1, and other conditions remain unchanged.
[0161] Example 13
[0162] The preparation process of Example 13 is basically the same as that of Example 8, except that in step 1), the ammonia value in the system is 4.3 g / L, the concentration of the precipitant is 18 mol / L, the pH value of the system is adjusted to 11.2, and other conditions remain unchanged.
[0163] Example 14
[0164] The preparation process of Example 14 is basically the same as that of Example 8, except that in step 1), the ammonia value in the system is 4.3 g / L, the concentration of the precipitant is 0.5 mol / L, the pH value of the system is 10.2, and other conditions remain unchanged.
[0165] Example 15
[0166] This embodiment provides a method for preparing a ternary cathode material. The preparation method includes the following steps:
[0167] In this embodiment, the nickel source is nickel sulfate, the M source is manganese sulfate, the cobalt source is cobalt sulfate, the complexing agent is ammonia, the precipitant is sodium hydroxide solution, the lithium source is lithium hydroxide, the dopants are zirconium dioxide and boron trioxide, and the coating layer material is aluminum trioxide and zirconium dioxide.
[0168] 1) Nickel source, cobalt source, M source, and water were mixed to obtain a salt solution with a total metal content of 2 mol / L, wherein nickel, cobalt, and manganese were mixed in a molar ratio of 0.8:0.1:0.1. The salt solution was placed in a reactor, and a precipitant and complexing agent were added to the salt solution to carry out a co-precipitation reaction. The concentration of ammonia water was 4 mol / L, the flow rate of ammonia water was 42 L / h, and the ammonia value in the system was controlled at 1.5 g / L. The pH value was adjusted using sodium hydroxide solution as a precipitant with a concentration of 4 mol / L and a flow rate of sodium hydroxide solution of 76 L / h, and the pH value of the system was adjusted to 11.8. During precipitation, uniform stirring was used to ensure uniform growth of material particles. The stirring speed was 300 r / min, and the water temperature was controlled at 55℃. After reacting for 36 h, the mixture was aged for 45 h to obtain the precursor Ni. 0.8 Co 0.1 Mn 0.1 (OH)2.
[0169] 2) Mix the precursor and lithium source at a molar ratio of 1:1.06, then add 500ppm B2O3 and 600ppm ZrO2 and mix evenly to obtain a mixture.
[0170] 3) Pass the mixture through a 200-400 mesh sieve, and then load the mixture into a sagger. Process it using the following sintering process: I. Sintering is divided into two stages, during which the oxygen concentration needs to be maintained above 90%. In the first sintering stage, the sintering temperature is 540℃, and the holding time is 8 hours. The second sintering temperature is 767℃, and the holding time is 15 hours, yielding the first sintered product.
[0171] 4) After crushing the first sintering product, mix it with water at a ratio of 1:1 and wash it for 3 minutes. The stirring speed is 600 r / min. After washing, filter the product by suction filtration to obtain a filter cake. Dry the filter cake at a certain temperature of 160℃.
[0172] 5) After drying, the first sintering product is crushed and sieved, and then mixed with the coating material. The specific addition ratio is 2300ppm Al2O3 and 3200ppm ZrO2. The mixture is mixed in a high-speed mixer for 15 minutes.
[0173] 6) The mixture obtained in step 5) is placed into a sagger and subjected to a second sintering. The temperature of the second sintering is 345℃, the holding time is 10 hours, and then the mixture is cooled to room temperature with the furnace. Finally, the mixture is cooled to room temperature with the furnace to obtain the ternary cathode material.
[0174] Example 16
[0175] The preparation process of Example 16 is basically the same as that of Example 15, except that the ammonia value in the system is 3.2 g / L in step 1), the pH value of the system is adjusted to 11.7, and other conditions remain unchanged.
[0176] Example 17
[0177] The preparation process of Example 17 is basically the same as that of Example 15, except that the ammonia value in the system in step 1) is 4 g / L, while other conditions remain unchanged.
[0178] Example 18
[0179] The preparation process of Example 18 is basically the same as that of Example 15, except that in step 1), the ammonia value in the system is controlled at 4.5 g / L and the pH value of the system is adjusted to 11.6, while other conditions remain unchanged.
[0180] Example 19
[0181] The preparation process of Example 19 is basically the same as that of Example 15, except that in step 1), the ammonia value in the system is controlled to be 5.8 g / L and the pH value of the system is adjusted to 11.9, while other conditions remain unchanged.
[0182] Example 20
[0183] The preparation process of Example 20 is basically the same as that of Example 15, except that in step 1), the ammonia value in the system is controlled at 3.8 g / L and the pH value of the system is adjusted to 12.7, while other conditions remain unchanged.
[0184] Example 21
[0185] This embodiment provides a method for preparing a ternary cathode material. The preparation method includes the following steps:
[0186] In this embodiment, the nickel source is nickel sulfate, the M source is manganese sulfate, the cobalt source is cobalt sulfate, the Al source is aluminum sulfate, the complexing agent is ammonia, the precipitant is sodium hydroxide solution, the lithium source is lithium hydroxide, the dopants are boron trioxide and cerium dioxide, and the coating layer material is zirconium dioxide and boron trioxide.
[0187] 1) Nickel source, cobalt source, M source, and water were mixed at a total metal content of 2 mol / L, with nickel, cobalt, manganese, and aluminum in a molar ratio of 0.88:0.07:0.03:0.02 to obtain a salt solution. The salt solution was placed in a reactor, and a precipitant and complexing agent were added to it for co-precipitation. The concentration of ammonia water was 3 mol / L, the flow rate of ammonia water was 40 L / h, and the ammonia concentration in the system was controlled at 4.3 g / L. The pH was adjusted using a sodium hydroxide solution as a precipitant, with a concentration of 5 mol / L and a flow rate of 65 L / h, to adjust the pH to 12.4. Uniform stirring was used during precipitation to ensure uniform particle growth at a stirring speed of 300 r / min and a water temperature of 55℃. After reacting for 36 h, the mixture was aged for 45 h to obtain the precursor Ni. 0.88 Co 0.07 Mn 0.03 Al 0.02 (OH)2.
[0188] 2) Mix the precursor and lithium source at a molar ratio of 1:1.06, then add 800ppm CeO2 and 800ppm B2O3 and mix evenly to obtain a mixture.
[0189] 3) Pass the mixture through a 200-400 mesh sieve, and then load the mixture into a sagger. Process it using the following sintering process: I. Sintering is divided into two stages, during which the oxygen concentration needs to be maintained above 90%. In the first sintering stage, the sintering temperature is 540℃, and the holding time is 8 hours. The second sintering temperature is 725℃, and the holding time is 15 hours, yielding the first sintered product.
[0190] 4) After crushing the first sintering product, mix it with water at a ratio of 1:1 and wash it for 3 minutes. The stirring speed is 600 r / min. After washing, filter the product by suction filtration to obtain a filter cake. Dry the filter cake at a certain temperature of 160℃.
[0191] 5) After drying, the first sintering product is crushed and sieved, and then mixed with the coating material. The specific addition ratio is 3000ppm ZrO2 and 2100ppm B2O3. The mixture is mixed in a high-speed mixer for 15 minutes.
[0192] 6) The mixture obtained in step 5) is placed into a sagger and subjected to a second sintering. The temperature of the second sintering is 345℃, the holding time is 10 hours, and then the mixture is cooled to room temperature with the furnace. Finally, the mixture is cooled to room temperature with the furnace to obtain the ternary cathode material.
[0193] Example 22
[0194] The preparation process of Example 22 is basically the same as that of Example 21, except that the pH value of the system is adjusted to 11.2 in step 1), while other conditions remain unchanged.
[0195] Example 23
[0196] The preparation process of Example 23 is basically the same as that of Example 21, except that the pH value of the system is adjusted to 10.3 in step 1), while other conditions remain unchanged.
[0197] Example 24
[0198] The preparation process of Example 24 is basically the same as that of Example 21, except that the pH value of the system is adjusted to 11.1 in step 1), the second sintering temperature is 900℃, and other conditions remain unchanged.
[0199] Example 25
[0200] The preparation process of Example 25 is basically the same as that of Example 21, except that the pH value of the system is adjusted to 11.3 in step 1), the second sintering temperature is 650℃, and other conditions remain unchanged.
[0201] Example 26
[0202] This embodiment provides a method for preparing a ternary cathode material. The preparation method includes the following steps:
[0203] In this embodiment, the nickel source is nickel sulfate, the M source is manganese sulfate, the cobalt source is cobalt sulfate, the Al source is aluminum sulfate, the complexing agent is ammonia, the precipitant is sodium hydroxide solution, the lithium source is lithium hydroxide, the dopants are cerium dioxide and boron trioxide, and the coating layer material is zirconium dioxide and boron trioxide.
[0204] 1) Nickel source, cobalt source, M source, and water were mixed at a total metal content of 2 mol / L, with nickel, cobalt, and aluminum in a molar ratio of 0.88:0.1:0.02 to obtain a salt solution. The salt solution was placed in a reactor, and a precipitant and complexing agent were added to it for co-precipitation. The concentration of ammonia water was 6 mol / L, the flow rate of ammonia water was 62 L / h, and the ammonia concentration in the system was controlled at 1.5 g / L. The pH value was adjusted using a sodium hydroxide solution as a precipitant, with a concentration of 6 mol / L and a flow rate of 80 L / h, adjusting the pH to 12.2. Uniform stirring was used during precipitation to ensure uniform particle growth at a stirring speed of 300 r / min, and the water temperature was controlled at 55℃. After reacting for 36 h, the mixture was aged for 45 h to obtain the precursor Ni. 0.88 Co 0.1 Al 0.02 (OH)2.
[0205] 2) Mix the precursor and lithium source at a molar ratio of 1:1.06, then add 800ppm CeO2 and 1000ppm B2O3 and mix evenly to obtain a mixture.
[0206] 3) Pass the mixture through a 200-400 mesh sieve, and then load the mixture into a sagger. Process it using the following sintering process: I. Sintering is divided into two stages, during which the oxygen concentration needs to be maintained above 90%. In the first sintering stage, the sintering temperature is 540℃, and the holding time is 8 hours. The second sintering temperature is 718℃, and the holding time is 15 hours, yielding the first sintered product.
[0207] 4) After crushing the first sintering product, mix it with water at a ratio of 1:1 and wash it for 3 minutes. The stirring speed is 600 r / min. After washing, filter the product by suction filtration to obtain a filter cake. Dry the filter cake at a certain temperature of 160℃.
[0208] 5) After drying, the first sintering product is crushed and sieved, and then mixed with the coating material. The specific addition ratio is 2200ppm B2O3 and 2100ppm ZrO2. The mixture is mixed in a high-speed mixer for 15 minutes.
[0209] 6) The mixture obtained in step 5) is placed into a sagger and subjected to a second sintering. The temperature of the second sintering is 345℃, the holding time is 10 hours, and then the mixture is cooled to room temperature with the furnace. Finally, the mixture is cooled to room temperature with the furnace to obtain the ternary cathode material.
[0210] Example 27
[0211] The preparation process of Example 27 is basically the same as that of Example 26, except that in step 1), the ammonia value of the system is controlled to be 3.1 and the pH value of the system is adjusted to 12, while other conditions remain unchanged.
[0212] Example 28
[0213] The preparation process of Example 28 is basically the same as that of Example 26, except that in step 1), the ammonia value of the system is controlled at 4.2 and the pH value of the system is adjusted to 12.1, while other conditions remain unchanged.
[0214] Example 29
[0215] The preparation process of Example 29 is basically the same as that of Example 26, except that in step 1), the ammonia value of the system is controlled to be 5.1 and the pH value of the system is adjusted to 12, while other conditions remain unchanged.
[0216] Example 30
[0217] The preparation process of Example 30 is basically the same as that of Example 26, except that the ammonia value of the system is controlled at 6 and the pH value of the system is controlled at 11.9 in step 1), while other conditions remain unchanged.
[0218] Example 31
[0219] This embodiment provides a method for preparing a ternary cathode material. The preparation method includes the following steps:
[0220] In this embodiment, the nickel source is nickel sulfate, the M source is manganese sulfate, the complexing agent is ammonia, the precipitant is sodium hydroxide solution, the lithium source is lithium hydroxide, the dopants are aluminum oxide and zirconium dioxide, and the coating layer material is aluminum oxide and boron oxide.
[0221] 1) A salt solution was prepared by mixing nickel source, M source, and water at a total metal content of 2 mol / L, with nickel and manganese in a molar ratio of 0.75:0.25. The salt solution was placed in a reactor, and a precipitant and complexing agent were added to carry out a co-precipitation reaction. The ammonia concentration was 7 mol / L, the ammonia flow rate was 35 L / h, and the ammonia concentration in the system was controlled at 3.8 g / L. The pH was adjusted using a sodium hydroxide solution as a precipitant at a concentration of 4 mol / L and a flow rate of 72 L / h, with the pH adjusted to 10.4. Uniform stirring was used during precipitation to ensure uniform particle growth at a stirring speed of 300 r / min and a water temperature of 55℃. After reacting for 36 h, the mixture was aged for 45 h to obtain the precursor Ni. 0.75 Mn 0.25 (OH)2.
[0222] 2) Mix the precursor and lithium source at a molar ratio of 1:1.06, then add 1500ppm Al2O3 and 3300ppm ZrO2 and mix evenly to obtain a mixture.
[0223] 3) Pass the mixture through a 200-400 mesh sieve, and then load the mixture into a sagger. Process it using the following sintering process: I. Sintering is divided into two stages, during which the oxygen concentration needs to be maintained above 90%. In the first sintering stage, the sintering temperature is 540℃, and the holding time is 8 hours. The second sintering temperature is 732℃, and the holding time is 15 hours, yielding the first sintered product.
[0224] 4) After crushing the first sintering product, mix it with water at a ratio of 1:1 and wash it for 3 minutes. The stirring speed is 600 r / min. After washing, filter the product by suction filtration to obtain a filter cake. Dry the filter cake at a certain temperature of 160℃.
[0225] 5) After drying, the first sintering product is crushed and sieved, and then mixed with the coating material. The specific addition ratio is 1500ppm B2O3 and 1300ppm Al2O3. The mixture is mixed in a high-speed mixer for 15 minutes.
[0226] 6) The mixture obtained in step 5) is placed into a sagger and subjected to a second sintering. The temperature of the second sintering is 345℃, the holding time is 10 hours, and then the mixture is cooled to room temperature with the furnace. Finally, the mixture is cooled to room temperature with the furnace to obtain the ternary cathode material.
[0227] Example 32
[0228] The preparation process of Example 32 is basically the same as that of Example 31, except that the pH value of the system is adjusted to 11.5 in step 1), while other conditions remain unchanged.
[0229] Example 33
[0230] The preparation process of Example 33 is basically the same as that of Example 31, except that the pH value of the system is adjusted to 12.3 in step 1), while other conditions remain unchanged.
[0231] Example 34
[0232] The preparation process of Example 34 is basically the same as that of Example 31, except that the pH value of the system is adjusted to 12.7 in step 1), while other conditions remain unchanged.
[0233] Comparative Example 1
[0234] The preparation process of Comparative Example 1 is basically the same as that of Example 3, except that the pH of the system is adjusted to 8.5 in step 1). Due to the low pH, secondary particles cannot be synthesized.
[0235] Comparative Example 2
[0236] The preparation process of Comparative Example 2 is basically the same as that of Example 3, except that the pH of the system is adjusted to 13.4 in step 1), while other conditions remain unchanged.
[0237] Comparative Example 3
[0238] The preparation process of Comparative Example 3 is basically the same as that of Example 15, except that: in step 1), the flow rate of ammonia water is 45 L / h, the ammonia value in the system is controlled at 8 g / L, the concentration of sodium hydroxide solution is 3 mol / L, the flow rate of sodium hydroxide solution is 78 L / h, the pH value is controlled within the range of 11.6, and other conditions remain unchanged.
[0239] Comparative Example 4
[0240] The preparation process of Comparative Example 4 is basically the same as that of Example 15, except that: in step 1), the flow rate of ammonia water is 45 L / h, the ammonia value in the system is controlled at 0.5 g / L, the concentration of sodium hydroxide solution is 3 mol / L, the flow rate of sodium hydroxide solution is 78 L / h, the pH value is adjusted to 11.8, and other conditions remain unchanged.
[0241] Comparative Example 5
[0242] The preparation process of Comparative Example 5 is basically the same as that of Example 21, except that: in step 1), the ammonia value in the system is controlled at 4.3 g / L and the pH value is 11.7, the aging step is omitted, and other conditions remain unchanged.
[0243] Comparative Example 6
[0244] The preparation process of Comparative Example 6 is basically the same as that of Example 15, except that: in step 1), the flow rate of ammonia water is 45 L / h, the ammonia value in the system is controlled at 4.3 g / L, the concentration of sodium hydroxide solution is 3 mol / L, the flow rate of sodium hydroxide solution is 78 L / h, the pH value is adjusted to 12.3, and in step 3), the second stage sintering temperature is 530℃. Due to the low sintering temperature, secondary particles cannot be prepared.
[0245] Comparative Example 7
[0246] The preparation process of Comparative Example 7 is basically the same as that of Example 15, except that: in step 1), the flow rate of ammonia water is 45 L / h, the ammonia value in the system is controlled at 4.3 g / L, the concentration of sodium hydroxide solution is 3 mol / L, the flow rate of sodium hydroxide solution is 78 L / h, the pH value is adjusted to 12.5, and in step 3), the second stage sintering temperature is 1000℃. Due to the excessively high sintering temperature, secondary particles cannot be prepared.
[0247] Test case
[0248] 1) Testing of the positive electrode material of lithium-ion batteries
[0249] The internal porosity P, pore size D, uniformity A, and surface roughness Z of the ternary cathode materials prepared in the above embodiments and comparative examples were measured. The measurement results are detailed in Table 1.
[0250] 2) Testing of lithium-ion batteries prepared with ternary cathode materials
[0251] The ternary cathode materials prepared in the above embodiments and comparative examples were respectively made into cathode sheets.
[0252] Positive electrode material: SP (conductive agent): KS-6 (conductive graphite): PVDF (polyvinylidene fluoride) = 94.5%: 2%: 1%: 2.5% plus NMP (N-methylpyrrolidone) to make positive electrode slurry, which is then coated and rolled to form positive electrode sheet.
[0253] The positive electrode, negative electrode, separator, and electrolyte were assembled into a 503048 model battery with a capacity of about 800mAh, which was then used for testing.
[0254] Cyclic testing: Charge and discharge at 1C, cut-off current of 0.05C, voltage range 2.8V-4.25V (Ni80 and above) 2.8~4.4V (Ni80 and below). Capacity retention rate after 300 cycles is calculated as the ratio of discharge capacity in the 300th cycle to discharge capacity in the first cycle. Ambient temperature 25℃±2℃.
[0255] Rate testing: Charge at 0.5C to the cutoff voltage, cutoff current 0.05C, discharge at 0.1C to 2.8V, charge and discharge for 3 cycles, and take the maximum discharge capacity; Charge at 0.5C to the cutoff voltage, cutoff current 0.05C, discharge at 1C to 2.8V, charge and discharge for 3 cycles, and take the maximum discharge capacity. Divide the 1C discharge capacity by the 0.1C discharge capacity to obtain the rate performance. Ambient temperature 25℃±2℃.
[0256] Gas production test: Charge to the cutoff voltage at 1C with a cutoff current of 0.05C. After fully charging, use the water displacement method to test the cell volume while maintaining the temperature at 25℃±2℃. Record the cell volume. Place the cell in a 70℃ environment for 7 days and test the cell volume again using the water displacement method, maintaining the water temperature at 70℃±3℃. After the cell volume test is completed, the ratio of the difference between the two volumes to the cell capacity is the gas production value.
[0257] The test results are detailed in Table 1.
[0258] Table 1 Performance characterization of cathode materials and lithium-ion batteries
[0259]
[0260]
[0261]
[0262] In Table 1, " / " indicates no data.
[0263] Comparative examples and comparative cases demonstrate that the cathode material provided by this invention, when applied to batteries, exhibits excellent performance in terms of cycle life, rate capability, and safety. The inventors believe that cathode materials possessing the aforementioned parameters such as internal porosity and surface roughness ensure sufficient contact with the electrolyte, resulting in shorter lithium-ion transport paths. Furthermore, minimizing the contact area between the cathode material and the electrolyte reduces side reactions and gas generation, thereby improving rate capability. Secondly, during rolling, it prevents secondary particles from being crushed, thus avoiding increased gas generation in the cathode sheet and improving cycle performance. In addition, the internal pores provide a buffer space for expansion / contraction during lithium insertion / extraction, preventing damage such as liquid swelling deformation of the cathode sheet and improving the safety performance of lithium-ion batteries.
[0264] The preparation method provided by this invention helps to control the surface roughness of secondary particles by adjusting the pH of the system to 10-13 and the concentration of complexing agent in the system to 1-6 g / L. Furthermore, the surface roughness of the secondary particles is further adjusted by aging, and then the surface roughness of the secondary particles is adjusted again by controlling the conditions of the second stage of sintering in the first sintering. As a result, the cathode material has excellent energy density, rate performance, cycle performance and safety performance.
[0265] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode material for a lithium-ion battery, characterized in that, The positive electrode material is composed of secondary particles, and the internal structure of the secondary particles has closed pores; the internal porosity P of the secondary particles is 2%≤P≤11%, and the surface roughness Z is 10nm≤Z≤500nm. The pore diameter D of the internal pores of the secondary particles is D≤2μm; The uniformity A of the internal pores of the secondary particles is 0.7 ≤ A ≤ 1.3; The method for calculating the uniformity A of the internal pores is as follows: the secondary particle is cut open, and the cross-section is called the cross-sectional circle. Concentric circles are drawn with the center of the cross-sectional circle as the center, and the diameter of the concentric circles is the radius of the cross-sectional circle. The pores in the concentric circles are identified, and the area S1 of these pores is calculated. The pores at the annulus between the cross-sectional circle and the concentric circles are identified, and the area S2 of these pores is calculated. The uniformity A of the internal pores is 3S1 / S2. The internal pores refer to the closed pores in the secondary particles. The cathode material includes a core material, the composition of which includes Li a Ni b Co c M 1-b-c O2, a is 0.8~1.2, b is 0.5~0.92, c is 0~0.5, and M is selected from at least one of Mn, Al, and V.
2. The cathode material according to claim 1, characterized in that, The cathode material also includes a coating layer that covers at least a portion of the surface of the core material.
3. A method for preparing the cathode material according to claim 1 or 2, characterized in that, The preparation method includes the following steps: 1) A precipitant and a complexing agent are introduced into a metal salt solution to make the concentration of the complexing agent in the system 3~5 g / L, and a co-precipitation reaction is carried out under the conditions of pH 11.9, 12 or 12.
2. After that, the mixture is aged to obtain the precursor of the cathode material. The complexing agent is ammonia water, the concentration of the ammonia water is 1~15 mol / L, the flow rate of the ammonia water is 10~500 L / h, the concentration of the precipitant is 1~10 mol / L, and the flow rate is 10~500 L / h; 2) The precursor is mixed with a lithium source and subjected to a first sintering to obtain a first sintering product; the first sintering is divided into a first stage sintering and a second stage sintering, the first stage sintering temperature is 300~600℃, the holding time is 1~15h, and the second stage sintering temperature is 650~900℃, the holding time is 3~20h; 3) The first sintering product is subjected to a second sintering to obtain the cathode material.
4. The preparation method according to claim 3, characterized in that, In step 1), the coprecipitation reaction is carried out under stirring at a rate of 200-500 r / min; and / or, In step 1), the temperature of the coprecipitation reaction is 45~70℃, and the time is 20~100 hours; And / or, In step 1), the salt solution contains a nickel source, a cobalt source and an M source, and the total concentration of nickel, cobalt and M metal ions is 0.5~3 mol / L.
5. The preparation method according to claim 3 or 4, characterized in that, In step 3), the first sintering product is first mixed with the coating material, and then a second sintering is performed.
6. A positive electrode plate, characterized in that, The positive electrode sheet comprises the positive electrode material according to claim 1 or 2, or the positive electrode material prepared by the preparation method according to any one of claims 3-5.
7. A lithium-ion battery, characterized in that, The lithium-ion battery includes the positive electrode sheet as described in claim 6.
Citation Information
Patent Citations
Vanadium pentoxide-coated core-shell structure gradient nickel-cobalt-manganese positive electrode material and preparation method
CN109546123A
Full-gradient nickel cobalt manganese cathode material, ruthenium oxide coating material and preparation method thereof
CN109980219A
